2003
DOI: 10.1634/stemcells.21-5-514
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Organ Engraftment by Bone‐Marrow‐Derived Myofibroblasts and Fibroblasts in Bone‐Marrow‐Transplanted Mice

Abstract: Myofibroblasts are ubiquitous cells with features of both fibroblasts and smooth muscle cells. We suggest that the bone marrow can contribute to myofibroblast populations in a variety of tissues and that this is exacerbated by injury. To assess this, female mice were transplanted with male bone marrow and the male cells were tracked throughout the body and identified as myofibroblasts. Skin wounding and paracetamol administration were used to assess whether myofibroblast engraftment was modulated by damage. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
176
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(184 citation statements)
references
References 30 publications
7
176
0
1
Order By: Relevance
“…Circulating bone marrow -derived cells contribute to the regeneration of a wide variety of organs. There is evidence that bone marrowderived stem cells are able to enter parenchymal organs and participate in regenerative and structural modeling of transplanted tissues [8,10,11,19] . However, the mechanism by which extrahepatic stem cells contribute to the repair process (including regeneration) following injury remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating bone marrow -derived cells contribute to the regeneration of a wide variety of organs. There is evidence that bone marrowderived stem cells are able to enter parenchymal organs and participate in regenerative and structural modeling of transplanted tissues [8,10,11,19] . However, the mechanism by which extrahepatic stem cells contribute to the repair process (including regeneration) following injury remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…For reprints contact: Reprints@AlphaMedPress.com 700 Bone Marrow-Derived Fibroblasts Recruited into Fibrotic Lesions transplantation of bone marrow (BM), hematopoietic stem cells or nonhematopoietic mesenchymal stem cells, muscle [7][8][9][10][11], heart [12][13][14], liver [15][16][17][18][19], vascular cells [20,21], and other mesenchymal cells [22][23][24] of donor origin have been detected. Investigators revealed that BM-derived cells can be progenitors for tissue fibroblasts that are recruited through the circulation to populate peripheral organs [25][26][27][28][29]. During renal fibrosis, a small number of fibroblasts were BM origin using BM chimera and transgenic reporter mice [25].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that cancer-induced stroma generated by the human pancreatic cancer cell line consist of BM-derived fibroblasts and that BM-derived fibroblasts become a major component of cancer-induced stromal cells in the later stage of tumor development [26]. Furthermore, BM-derived fibroblasts were engrafted into multiple organs, and it was found that these cells are recruited into injured tissue [27,28]. However, the phenotype and functional roles of BM-derived fibroblasts have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver injury results in HSC activation switching HSCs to a myofibroblast phenotype and collagen secretion. During the development of fibrosis in diverse organs, we and others have shown that BM contributes to the myofibroblast population (usually between 20% and 30%) in diverse organs, 6 using experimental models of liver disease [7][8][9] and studies of human liver tissue. 10 Interestingly, we have also noted a relative lack of BM-derived ␣-smooth muscle actinpositive myofibroblasts during liver fibrosis regression, 9 and the results from Higashiyama et al may reflect the tissue analysis being restricted to a narrow timeframe.…”
Section: Replymentioning
confidence: 99%
“…1 We totally agree that BM contains pluripotential stem/progenitor cells and diverse cell types with different functions. 2 In contrast to the beneficial role of BMderived cells in the resolution of fibrosis, a number of experimental and human studies using BM transplantation with sex-mismatched 3,4 or genetically marked cells 5,6 have indicated that they express collagen and participate in the progression of liver fibrosis. In this study, we performed a series of confocal laser scanning microscopy examinations using the emission fingerprinting method, which eliminated the background autofluorescence and detected only the specific fluorescent signals.…”
Section: Replymentioning
confidence: 99%